The heterogeneity-diversity-system performance nexus - Eisenhauer, Nico; Angst, Gerrit; Asato, Ana E B; Beugnon, Rémy; Bönisch, Elisabeth; Cesarz, Simone; Dietrich, Peter; Jurburg, Stephanie D; Madaj, Anna-Maria; Reuben, Rine C; Ristok, Christian; Sünnemann, Marie; et al. (National science review, 2023)
Ever-growing human population and nutritional demands, supply chain disruptions, and advancing climate change have led to the realization that changes in diversity and system performance are intimately linked. Moreover, diversity and system performance depend on heterogeneity. Mitigating changes in system performance and promoting sustainable living conditions requires transformative decisions. Here, we introduce the heterogeneity-diversity-system performance (HDP) nexus as the conceptual basis upon which to formulate transformative decisions. We suggest that managing the heterogeneity of systems will best allow diversity to provide multiple benefits to people. Based on ecological theory, we pose that the HDP nexus is broadly applicable across systems, disciplines, and sectors, and should thus be considered in future decision making as a way to have a more sustainable global future.
Keywords: biodiversity-ecosystem functioning; global change; heterogeneity; homogenization; diversity